Evolving Market Dynamics and Investor Behavior: Lessons from the Pandemic's Impact on Saudi Arabia's Financial Landscape - Alamir, Ibrahim (مجلة العلوم الإدارية و الإقتصادية, 2025)
This study delves into the intricate dynamics of the Saudi stock market, specifically the Tadawul All Share Index (TASI), during the COVID-19 pandemic. It explores the multifaceted relationship between investor sentiment and market responses, considering various influential factors such as local market confidence, regional stability, and government policies. Through a comprehensive analysis of TASI's performance in comparison to major global indices like the Dow Jones, NASDAQ, and S&P 500, the study reveals unique market behaviors and the relative resilience of the Saudi market amidst global economic upheaval. Key findings include the TASI's ability to maintain stability despite global volatility, with a low to moderate positive correlation with these global indices and a 15% increase in trading volume during key intervention periods. The significant impact of the Saudi government’s economic and public health measures on stabilizing the market is also highlighted. The study's timeframe spans from January 2020 to November 2023, offering a timely insight into the market's adaptation to an unprecedented global crisis. The research contributes to a deeper understanding of the Saudi stock market's dynamics during the pandemic, providing valuable insights for investors, policymakers, and the broader Saudi economy.